Bioavailability and Efficacy of a Gap Junction Enhancer (PQ7) in a Mouse Mammary Tumor Model - Shishido, Stephanie N. (Public Library of Science, 2013)
The loss of gap junctional intercellular communication is characteristic of neoplastic cells, suggesting that the restoration with a gap junction enhancer may be a new therapeutic treatment option with less detrimental effects than traditional antineoplastic drugs. A gap junction enhancer, 6-methoxy-8-[(2-furanylmethyl) amino]-4-methyl-5-(3-trifluoromethylphenyloxy) quinoline (PQ7), on the normal tissue was evaluated in healthy C57BL/6J mice in a systemic drug distribution study. Immunoblot analysis of the vital organs indicates a reduction in Cx43 expression in PQ7-treated animals with no observable change in morphology. Next the transgenic strain FVB/N-Tg(MMTV-PyVT) 634Mul/J (also known as PyVT) was used as a spontaneous mammary tumor mouse model to determine the biological and histological effects of PQ7 on tumorigenesis and metastasis at three stages of development: Pre tumor, Early tumor, and Late tumor formation. PQ7 was assessed to have a low toxicity through intraperitoneal administration, with the majority of the compound being detected in the heart, liver, and lungs six hours post injection. The treatment of tumor bearing animals with PQ7 had a 98% reduction in tumor growth, while also decreasing the total tumor burden compared to control mice during the Pre stage of development. PQ7 treatment increased Cx43 expression in the neoplastic tissue during Pre-tumor formation; however, this effect was not observed in Late stage tumor formation. This study shows that the gap junction enhancer, PQ7, has low toxicity to normal tissue in healthy C57BL/6J mice, while having clinical efficacy in the treatment of spontaneous mammary tumors of PyVT mice. Additionally, gap junctional intercellular communication and neoplastic cellular growth are shown to be inversely related, while treatment with PQ7 inhibits tumor growth through targeting gap junction expression.